Knowledge about crime scenes and evidence management among emergency medical team professionals - Mayada A. Daibes; Mohammad R. Alsadi; Majed M. Alruwaili; Mohammad Y. Alzaatreh; Majd T. Mrayyan; Hamzeh Y. Abunab; Mohammad J. ALhemedi (BMC Emergency Medicine)
Abstract Background To ensure that no criminal evidence has been moved or destroyed from the crime scene, emergency medical team (EMT) professionals should receive appropriate training, particularly in recognizing, collecting, preserving, and documenting evidence in both prehospital and intrahospital environments. Aim To assess the knowledge and practices of EMT professionals in recognizing, collecting, preserving, and documenting criminal evidence. Method A cross-sectional design utilizing an online survey was used to collect data from EMT professionals, including nurses, paramedics and physicians. Healthcare settings, including governmental, private, civil defense, and military hospitals in Jordan, participated in the study. Results A total of 441 EMT professionals participated in the study. EMT professionals in Jordan had “moderate” levels of knowledge about recognizing and collecting forensic evidence. Moreover, their knowledge of preserving it was relatively low. The levels of knowledge were higher among physicians and paramedics compared to nurses, as well as in military and private hospitals compared to governmental ones. On the other hand, EMT professionals did perform well in documenting forensic evidence. Conclusion Integrating the topics of forensic medicine into the undergraduate educational preparation of EMT professionals is essential. This extends to the continuous educational efforts taking place in healthcare settings, as well as highlighting them in the job descriptions of healthcare professionals, particularly in the emergency department. A graduate degree and specialization in forensic medicine are also required for EMTs in Jordan.